فعالية تطبيق اللغة الحروف المتسلسلة (Head and Tail) في ترقية مهارة الكلام - Fauzi, Ahmad; Junaedi; Isnainiyah; Sholihah, Hilmiyatus; Alisha, Marya Alvina (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Each language has four skills, namely listening, speaking, reading and writing. In learning a foreign language we are led to be proficient in every skill.  Likewise in speaking skills. Language games are used to make it easier for students to understand the material presented and make students more innovative in learning the language. One of the language games that are considered interesting in learning Arabic is Head and Tail.  This game is a way of learning that requires students to learn a lot of talk and a lot of vocabulary.  Besides, students will be more enthusiastic, and improve students' speaking skills.  This study was well received by class VIII A students. But on the other hand, before learning begins, it is better to introduce vocabulary related to the material. The purpose of this study was to determine the application of the Head and Tail game in improving the speaking ability of students of class VIII A MTs An Nasyiin PP.  Mas and to find out the effectiveness of the application of the Head and Tail game, the Head and Tail game for class VIII A students at MTs An Nasyiin PP.  Mas Krembangan Taman Sidoarjo using quantitative research.  The data collection of this research was carried out using the following methods: 1) observation, 2) interviews, 3) documentation, and 4) tests. The results of learning to train Arabic speaking skills for class VIII A students at MTs An Nasyi'in Pondok Pesantren Mas Krembangan Taman Sidoarjo with increased Head and Tail, this can be seen from the scores obtained by students from before the application of "the application of the Head and Tail game with a score of 67.65 and after the application of the Head and Tail game 83.24.  For this reason, it is recommended for Arabic teachers to apply and develop learning using Head and Tail games or other media for the success of learning Arabic